The Role of the Al-Hidayah Taklim Council in Forming Social Harmony in the Community in Karanganyar Village, Bantaran District, Probolinggo Regency - Fatimatus Zahro; Khoiriyah Khoiriyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study focuses on the role of Majelis Taklim Al-Hidayah in Krajan Hamlet, Karanganyar Village, Bantaran District, Probolinggo Regency in shaping and strengthening social harmony within rural communities. The objective is to reveal how the religious and social activities of the Majelis contribute to building strong social bonds amidst the challenges of modernization, characterized by increasing individualism and declining quality of social interaction. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, documentation, and literature review, and analyzed using Miles and Huberman’s interactive model through the stages of data reduction, data display, and conclusion drawing. The findings indicate that Majelis Taklim Al-Hidayah functions not only as a forum for religious learning but also as a space for strengthening social ties through Qur’anic recitation, social gatherings, and mau’izhah hasanah (religious advice). It serves as an intergenerational arena that enhances communication across age groups, social solidarity, and community participation. The active role of women as the main driving force reflects a social transformation rooted in religious values. Strategies such as rotational hosting, consensual decision-making, and collective fund management have proven effective in reinforcing social cohesion and fostering a harmonious collective culture. These findings affirm that Majelis Taklim Al-Hidayah plays a significant role as a socio-religious agent capable of preserving harmony and solidarity in rural communities while enriching the understanding of the socio-religious functions of local Islamic institutions amid the currents of modernization.